Ministers Manual 1982 Edition - Cox, James W. (James William) (Cambridge Harper & Row, 1982)
The all-new Ministers Manual, the most comprehensive resource for preachers, features 250 sermons and sermon outlines--the best of traditional and contemporary sources to assist in sermon preparation and to ignite the minister's imagination. "An excellent
Keywords: Sermons -- Outlines, syllabi, etc. Homileticical illustrations. Church year -- Manual, handbook, etc